"To witness facts with the eyes of reason": Herschel on physical astronomy and the method of residual phenomena - Miyake, Teru (Springer, 2023)
The aim of this chapter is to argue for the following claim. In the “Physical Astronomy”, Herschel takes the whole difficulty of physical astronomy to be dealing with the complexity of the planetary motions, and describes a method for dealing with these complexities that is neither inductive nor hypothetico-deductive. In this method, the primary use of theory is as a tool that allows the skilled practitioner to separate out the various effects that together make up the complex planetary motions, and identify details in the solar system that give rise to them. Although Herschel does not use the term “residual phenomena” in the “Physical Astronomy”, these complexities in the orbital motions are prime examples of what he would later come to call residual phenomena.